Preparation of Tris(dimethyldithiocarbamato) Iron(III) and its Effect on Seed Germination - Arora, C.L.; Kaur, Jaswinder (Asian Journal of Chemistry, 2010)
Tris(dimethyldithiocarbamato) iron(III) has been prepared from the corresponding sodium salt by the reaction with ferric chloride, in dichloromethane/water medium. When moong (Phaseolus mungo) seeds are treated with dilute solutions of the complex in chloroform, there is a marginal increase in the metabolic activity.